If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + -11 = 7x + 6 Reorder the terms: -11 + 2x = 7x + 6 Reorder the terms: -11 + 2x = 6 + 7x Solving -11 + 2x = 6 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -11 + 2x + -7x = 6 + 7x + -7x Combine like terms: 2x + -7x = -5x -11 + -5x = 6 + 7x + -7x Combine like terms: 7x + -7x = 0 -11 + -5x = 6 + 0 -11 + -5x = 6 Add '11' to each side of the equation. -11 + 11 + -5x = 6 + 11 Combine like terms: -11 + 11 = 0 0 + -5x = 6 + 11 -5x = 6 + 11 Combine like terms: 6 + 11 = 17 -5x = 17 Divide each side by '-5'. x = -3.4 Simplifying x = -3.4
| 36=w+5w | | 5(8+7x)=390 | | -6x+4(x+8)=30 | | 5a-3whena=4 | | 12u-5u=56 | | F(8)=10-2x | | a^2+12a-47=0 | | 32=8v+5(v-4) | | 6(x+2)-2x=28 | | X-pie=pie | | 2(x+8)=-2x | | 2sin(-x)=0 | | 10(1+36)=20 | | x^4+x^2=684 | | -5.5+3.5(1-4s)=-20.5 | | tan63=34/x | | 15000=50*x^2/2 | | 3-(4x-2)=27 | | 3y^2-11y-16=0 | | 18=8v-4(v+8) | | (4x+3)(x)=320 | | 6n+3=3[-7n+1] | | (4x+5)(x)=400 | | 4+6[6-3n]=-5n-25 | | g^2+11g-152=0 | | -5u=-6u+6 | | (x+3)-3(x-2)=16 | | -f=f+10 | | 6x-7y+3x-2y= | | x^2-42y^2=1 | | 9+8b=9b | | -20+14x=10x+16 |